Greek Cypriot Students’ Attitudes toward Turkish Cypriots and the Open Crossing Points across the Green Line - Konstanta, Kyriakos (Department of Communication and Internet Studies, Faculty of Communication and Media Studies, Cyprus University of Technology, 2019)
This research aimed on measure the attitudes of Greek Cypriot university students towards Turkish Cypriots and towards the open crossing points and on explaining the adoption of these attitudes using sociological theory. This was achieved through the distribution of questionnaires in both digital and printed form to 244 students at the Cyprus University of Technology, which measured attitudes towards Turkish Cypriots and the open crossing points, as well as specific personality traits, as the sociological theories chosen suggest. An in-depth analysis was also pursued with ten semi-structured interviews with students. Lack of contact with Turkish Cypriots, authoritarian personality traits, tendency to scapegoat and personal interest appear to be factors that directly affect these attitudes.
Keywords: Contact Hypothesis; Authoritarian personality; Rational choice; Post-conflict societies; Peace-building; Cyprus Problem